Response of flooded rice cultivars to nitrogen as affected by row spacing, seed rate and weed control - Alvarenga, Marco António Rezende; Aquino, António Renes Lins de; Stone, Luis Fernando; Ajimura, Goes Matsutaro; Silveira Filho, Austrelino (Pesquisa Agropecuaria Brasileira, 2014)
Two field experiments were carried out to determine the influence of row spacing, seed rate and weed control on the response of rice cultivars to nitrogen. In one experiment four levels of nitrogen (O, 40, 80 and 120 kg/ha of N, three seed rates (300, 400 and 500 seeds/m2), two cultivars (’IAC 435’ and ’IR 841-63-5-L-9-33’), two row spacings (20 and 40 cm) and seed broadcast were studied. The treatments in the second experiment included three levels of nitrogen (0, 60 and 120 kg/ha of N), two row spacings, two cultivars, three methods of weed control (oxadiazon, propanil and weeding) and a check without weed control. The row spacings and cultivars were the same as in the first experiment. There was no significant difference in grain yield between the seed rate of 300 seeds/m2 and higher rates (400 and 500 seeds/m2). The former was considered best. The row planting yielded more than broadcast exhibiting no significant difference between the row spacings of 20 and 40 cm. The nitrogen levels of 65 kg/ha N and 85 kg/ha N in the cultivars ‘IAC 435’ and ’IR 841-63-5-L-9-33’ respectively resulted in maximum grain yields. Both the herbicides tested gave good control of weeds.